Evaluation of Malolactic Bacteria Isolated from Oregon Wines - Henick-Kling, T. (1989)
Oregon is a cool wine-producing region where grapes characteristically contain high concentrations of organic acids. To reduce the natural acidity and increase the microbiological stability and flavor complexity of the wine, malolactic fermentation is encouraged. In this study, strains of Leuconostoc oenos indigenous to Oregon wines were evaluated for their suitability to conduct malolactic fermentation in Oregon wines. Tests determined the malolactic activity of the Oregon isolates in comparison with commercial strains ML-34, PSU-1, MLT-kli, and ens 44-40 under various temperature and pH conditions. Sensitivities to sulfur dioxide, ethanol, and fumaric acid also were determined. Two Oregon strains, Er-1a and Ey-2d, were selected for commercial winemaking tests because they had greater malolactic activity under conditions of low pH (3.0) and low temperature (15 and 8°C), respectively.